HBR's 10 must reads on high performance. (Boston, Massachusetts : Harvard Business Review Press, 2022)
"Identify what's holding you back. Take care of your physical health for sustained mental performance. Understand what motivates you. Inspire others to reach their potential"--
The Making of an Expert / by K. Anders Ericsson, Michael J. Prietula, and Edward T. Cokely -- Managing Oneself / by Peter F. Drucker -- Are You a High Potential? / by Douglas A. Ready, Jay A. Conger, and Linda A. Hill -- Making Yourself Indispensable / by John H. Zenger, Joseph R. Folkman, and Scott K. Edinger -- How to Play to Your Strengths / by Laura Morgan Roberts, Gretchen Spreitzer, Jane Dutton, Robert Quinn, Emily Heaphy, and Brianna Barker Caza -- The Power of Small Wins / by Teresa M. Amabile and Steven J. Kramer -- Nine Things Successful People Do Differently / by Heidi Grant -- Make Time for the Work That Matters / by Julian Birkinshaw and Jordan Cohen -- Don't Be Blindsided By Your Own Expertise / by Sydney Finkelstein -- Mindfulness in the Age of Complexity / by Ellen Langer and Alison Beard -- Primal Leadership: The Hidden Driver of Great Performance / by Daniel Goleman, Richard Boyatzis, and Annie McKee -- Bounus Digital Article: The Right Way to Form New Habits / by James Clear and Alison Beard.
Includes index.
Description based on online resource; title from digital title page (viewed on August 15, 2022).
WorldCat record variable field(s) change: 650
Keywords: Work -- Psychological aspects; Performance; Success in business; Performance technology; Task Performance and Analysis; Travail -- Aspect psychologique; Rendement au travail; Succès dans les affaires; Performance; Success in business; Work -- Psychological aspects